Empiricism, Early Modern - Calvente, Sofía (2020)
Broadly speaking, "empiricism" is a label that usually denotes an epistemological view that emphasizes the role that experience plays in forming concepts and acquiring and justifying knowledge. In contemporary philosophy, there are some authors who call themselves as empiri- cists, although there are differences in the way they define what experience consists in, how it is related to theory, and the role experience plays in discovering and justifying knowledge, etc. (e.g., Ayer 1936; Van Fraassen 2002). In contrast, in the early modern period, empiricism was not a label that philosophers traditionally characterized until nowadays as empiricists (most famously, John Locke, George Berkeley, and David Hume) used to describe their doctrines. Indeed, as attributed to early modern philosophical authors, empiricism is not an actor's category, but an analytic historio- graphical category retrospectively applied to them and confronted to rationalism, whose main repre- sentatives were considered to be Rene Descartes, Baruch Spinoza, and G.W. Leibniz. Such a narrative began to be established by the late nineteenth- century and described early modern empiricism as an epistemological stance maintaining (1) that the origin of all mental contents lies in experience (a genetic statement), and (2) that knowledge can only be justified a posteriori (an epistemic state- ment). This entails that empiricists deny the existence of innate mental contents and the possibility of a purely a priori knowledge. In the history of early modern science such a dichotomy has been usually rendered in terms of the opposition between conti- nental rationalist Cartesian science vs British empir- icist Newtonian science. In the last four decades, many aspects of this traditional narrative have been criticized, and the meaning of early modern empiri- cism is subject of renewed studies.